Pengembangan Paket Bimbingan Perencanaan Studi Lanjut dengan Model Creative Problem Solving Bagi Siswa Sekolah Menengah Atas - Nadiarenita, Agrery Ayu; Muslihati, Muslihati; Hotifah, Yuliati (Jurnal Kajian Bimbingan dan Konseling, 2024)
This study aims to produce a package of guidance planning further studies with a model of creative problem solving for high school students who meet the acceptability aspects are aspects accuracy, usability, convenience and attractiveness. The guidance package consists of counselors guide book that contains the steps to the stage of providing guidance in career planning and student guide book that contains the materials and evaluation. The research method was adapted from models of Research and Development (R & D) procedural Borg & Gall (1983). Experts and field trials is limited (potential users) are analyzed using inter-rater agreement models (Gregory, 2011). Test validity index subject matter experts, media and potential users counselor showed very high criteria. These products meet very precise criteria, very useful, very easy and very attractive to mean very feasible to use. Based on the test can be concluded that the guidance package product planning further studies have met the acceptance criteria.